2010
DOI: 10.1016/j.biomaterials.2010.03.072
|View full text |Cite
|
Sign up to set email alerts
|

The magnetophoretic mobility and superparamagnetism of core-shell iron oxide nanoparticles with dual targeting and imaging functionality

Abstract: With the goal to achieve highly efficacious MRI-monitored magnetic targeting, a novel drug carrier with dual nature of superior magnetophoretic mobility and superparamagnetism was synthesized. This carrier was specially designed in a core-shell structure. The core was achieved by utilizing a strategy of self-assembly of oppositely charged ultrafine superparamagnetic iron oxide nanoparticles previously prepared. The final particles were formed by coating such cores with carboxymethyldextran (CMD) polymer. By ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 25 publications
1
44
0
Order By: Relevance
“…The purified sample corresponding to the lowest pressure (C1WP, 20 mbar), with 56 Oe coercive field and ratio of remnant to saturation magnetization of only 4.9 at 300 K may be considered as approaching the characteristics of super-paramagnetic particles. all measurements [22], in stark contrast to other thermal plasma synthesized magnetic nanomaterials [19]. However, the average size was actually measured from a distribution of sizes with a tail representing bigger particles whose contribution is also inevitably present in the results.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The purified sample corresponding to the lowest pressure (C1WP, 20 mbar), with 56 Oe coercive field and ratio of remnant to saturation magnetization of only 4.9 at 300 K may be considered as approaching the characteristics of super-paramagnetic particles. all measurements [22], in stark contrast to other thermal plasma synthesized magnetic nanomaterials [19]. However, the average size was actually measured from a distribution of sizes with a tail representing bigger particles whose contribution is also inevitably present in the results.…”
Section: Methodsmentioning
confidence: 99%
“…In order to avoid serious particle agglomeration inside living tissues, the encapsulated nanoparticles should possess superparamagnetic properties, which may be achieved only when the particle is smaller than the ϰ critical domain size. On the other hand, very small particles may be quickly eliminated by the renal filtration system of the living body [22]. Empirically, it has been always observed that saturation magnetization possessed by a CEMN decreases with decreasing encapsulated core particle size, which is an important parameter for proper process control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Briefly, samples (about 0.5 mg Fe/mL) were well dispersed in deionized water and placed into a 1 cm × 1 cm quartz cuvette fixed on the inner plate of a Dynal magnetic separator. Next, 10 µL aliquots were withdrawn at preset time points for measurement of iron content using inductively coupled plasma optical emission spectroscopy.…”
Section: Magnetophoretic Mobilitymentioning
confidence: 99%
“…It might turn out particularly useful for biomedical in vivo applications in diagnostic applications such as MRI [1] and therapies such as sitespecific drug delivery [2,3] and magnetic particle hyperthermia [4,5]. MCNCs, in a form of microparticles (or microspheres), with embedded magnetic cores are especially proposed for in vitro applications [6,7] e.g.…”
Section: Introductionmentioning
confidence: 99%